Ocean surface currents estimated from satellite remote sensing data based on a global hexagonal grid - Wenbo Wang; Huijun Zhou; Senyuan Zheng; Guonian Lü; Liangchen Zhou (International Journal of Digital Earth, 2023)
Global ocean surface currents estimated from satellite derived data based on a regular global grid are affected by the grid’s shape and placement. Due to different neighbourhood relationships, the rectangular lat/lon grids lose accuracy when interpolating and fitting elevation data. Hexagonal grids have shown to be advantageous due to their isotropic, uniform neighbourhood. Considering these merits, this paper aims to estimate global ocean surface current using a global isotropic hexagonal grid from satellite remote sensing data. First, gridded satellite altimeter data and wind data with different resolutions are interpolated into the centre of the global isotropic hexagonal grid. Then, geostrophic and Ekman currents components are estimated according to the Lagerlof Ocean currents theory. Finally, the inversion results are verified. By analyzing the results, we conclude that the ocean surface currents estimated based on the global isotropic hexagonal grid have considerable accuracy, with improvement over rectangular lat/lon grids.